Catalytic Performance of La-Ni/Al2O3 Catalyst for CO2 Reforming of Ethanol - Mahadi, Bahari; Vo, Dai-Viet N.; Nguyen, Huu Huy Phuc; Nurul Aini, Razali (2015)
Bio-derived ethanol has been considered as an attractive and alternative feedstock for dry or steam reforming reactions to generate renewable hydrogen, which may be used for replacement of conventional fossil fuels. Ethanol dry reforming (EDR) is an environmentally-friendly process since it transforms greenhouse gas, CO2 to value-added products and ethanol can be easily obtained from biomass which is free of catalyst poisons (i.e. sulphur-containing compounds). However, there are currently limited studies regarding syngas production from EDR [1, 2]. Ni-based catalysts are commonly used for reforming reactions due to its capability of C-C bond rupture, relatively low cost and high availability compared to precious metals [2]. Nevertheless, carbonaceous deposition may considerably deteriorate catalytic activity and stability of Ni-based catalysts. La promoter reportedly hindered carbon deposition and improved catalytic activity [3]. Hence, the objective of this research was to investigate the effect of La promotion on 10%Ni/Al2O3 catalyst for EDR.